Resource allocation and romantic jealousy: An experimental test of sex differences using economic games - Fernandez-Tapia, A; Barbato-Epple, M (ELSEVIER SCIENCE INC, 2026)
Romantic jealousy is theorized to have evolved as an adaptive mechanism triggered by sex-specific threats to reproductive fitness. In men, sexual infidelity poses risks of paternal uncertainty, whereas in women, emotional infidelity threatens resource diversion. To test evolutionary predictions about sex differences in jealousy responses, the present study employed an improved economic game paradigm with heterosexual couples. Specifically, the modified dictator game was refined to explicitly state that the participant s partner would not only allocate resources to a newly introduced intrasexual rival but also receive resources that the partner would directly accept from this rival, thereby clarifying the intentionality and directionality of the exchange. This adjustment enhances ecological validity by modeling both partner-initiated and rival-initiated threats in a more realistic mate-poaching context. Seventy-nine heterosexual couples participated in a laboratory setting. Controlling for individual differences such as attachment anxiety and digital jealousy, it was hypothesized that women would experience greater jealousy than men when their partner allocated resources to a rival, while men would experience greater jealousy than women when their partner received resources from a rival to the detriment of the rival s partner. Results partially supported these hypotheses: resource allocation to a rival triggered greater jealousy responses in all participants, particularly among women, consistent with emotional infidelity models, whereas the reception condition yielded weaker and less differentiated effects. These findings suggest that allocation-based paradigms effectively model generalized romantic jealousy in partner-rival contexts involving resource exchange but may have limited sensitivity for detecting mate-poaching-related jealousy. More broadly, the study highlights the promise and constraints of economic games for experimentally investigating sex-specific adaptations in emotional responses.